Y-B-P-R or S-C-C′? Suggestion for the nomenclature of experimental brittle fault fabric in phyllosilicate-granular mixtures. (December 2022) - Volpe, G.; Pozzi, G.; Collettini, C.
Abstract: Mineralogy, fabric, and frictional properties are fundamental aspects of faults. Despite the extensive effort spent in the characterization of such fault properties, the description of fabric elements is not always univocal and nomenclatures such as the Y-B-P-R and the S-C-C′ are at times used interchangeably. This work presents a systematic mineralogical, microstructural, and frictional characterization of natural gouges designed to constrain a criterion for the distinction between the Y-B-P-R and S-C-C′ fabric. For this purpose, we tested four representative natural mixtures of granular minerals (quartz) with increasing amount of phyllosilicates (muscovite). 24 frictional experiments were performed at constant normal stresses of 25, 50, 75 and 100 MPa, at both room dry and water saturated condition. We document that Y-B-P-R fabric typically develops in frictionally strong, granular-rich experimental faults. This fabric is associated to strain localization in narrow shear zones characterized by intense grain size reduction and dominant cataclastic processes. Conversely, S-C-C′ fabric is observed in phyllosilicate-rich experimental faults, which are characterized by distributed deformation and pervasive foliation. Deformation is mainly accommodated by frictional sliding along the well-oriented phyllosilicate foliae. The transition from Y-B-P-R to S-C-C′ is observed for phyllosilicates content >30% and is facilitated by secondary mechanical processes as networking of phyllosilicates and grain mantling. The evolution from Y-B-P-R to S-C-C′ fabric is also associated with a marked reduction in friction, in healing rate and changes in the rate and state friction parameters. Despite their geometrical similarities, we show that Y-B-P-R and S-C-C′ represent distinct fabrics reflecting the dichotomy that exists between frictionally strong, granular-rich, and frictionally weak, phyllosilicate-rich faults. Highlights: Y-B-P-R and S-C-C′ represent endmember fabrics of brittle laboratory faults. Y-B-P-R fabric forms in granular-rich materials deforming by cataclastic processes. S-C-C′ fabric forms in phyllosilicate-rich materials mainly deforming by frictional sliding. Fabric and mineralogy control the frictional properties of experimental faults.